Production of membranes for filtration of biomolecules - Castilho, Pedro Henrique Barata (2018)
Made available in DSpace on 2018-03-28T15:59:21Z (GMT). No. of bitstreams: 1 3687_7390.pdf: 3867360 bytes, checksum: 27c34357e979a708a30b4d265998d898 (MD5) Previous issue date: 2014-10-31